"I Am Here": Investigating the Relationship Between Sense ofDirection and Communication of Spatial Information. (September 2022) - Cauffman, Stephen; Cohen, Myke C.; Yin, Xiaoyun; Demir Federico Scholcover, Mustafa; Huang, Lixiao; Cooke, Nancy
Navigation is critical for everyday tasks but is especially important for urban search and rescue (USAR) contexts. Aside from successful navigation, individuals must also be able to effectively communicate spatial information. This study investigates how differences in spatial ability affected overall performance in a USAR task in a simulated Minecraft environment and the effectiveness of an individual's ability to communicate their location verbally. Randomly selected participants were asked to rescue as many victims as possible in three 10-minute missions. Results showed that sense of direction may not predict the ability to communicate spatial information, and that the skill of processing spatial information may be distinct from the ability to communicate spatial information to others. We discuss the implications of these findings for teaming contexts that involve both processes.